Development of Electronic Student Worksheet Based on Problem-Based Learning for Material on Environmental Change Geoheritage Gumuk Pasir - Handayani, Nida Dwi; Djukri (Jurnal Penelitian Pendidikan IPA, 2024)
This research aims to determine the development of PBL-based electronic LKPD on environmental change material at Gumuk Pasir Geoheritage and the feasibility of PBL-based electronic LKPD on class X environmental change material at Gumuk Pasir Geoheritage. This research is development research (R&D) using a 4D development model consisting of stages definition, design, development and deployment. This research was only carried out until the development stage. This research was validated internally by media expert lecturers and material experts and externally validated by biology teachers and class X high school students. The results of the research show that based on the assessment of media expert lecturers, a score of 82.13 was obtained in the "very good" category, material experts received a score of 67.4 in the "good" category, biology teachers obtained a score of 92.84 in the "very good" category, and the assessment of class X high school students obtained a score of 94.44. “very good” category. Based on the results of the development and feasibility that have been carried out, it can be concluded that the PBL-based electronic LKPD is suitable for use in the learning process regarding environmental change material at the Gumuk Pasir Geoheritage.